Application of the Theory of Planned Behavior for the Prevention of Substance Abuse among Male Adolescents - Isa Mohammadi Zeydi; Amir Pakpour-Hagiagha (Iranian Association of Health Education and Health Promotion, 2016)
Background and objective: Adolescence is the most dangerous of lifetime regarding the onset of substance abuse and education is one of the most important methods to prevent this problem. The purpose of this study was to determine the impact of an educational intervention in the prevention of substance abuse among adolescents in Qazvin city using the theory of planned behavior (TPB). Materials and methods: This study was a quasi-experimental study. With multi-stage sampling method, 216 students participated in the experimental and control groups. Five focus group discussions (including 8-15 members) were presented to the experimental group mainly based on role-playing, brain storming and group discussions methods. Self-reporting questionnaires were used for data collection consisted of demographic questions, attitudes, subjective norms, perceived behavioral control, intention and preventive behavior with 5-point Likert response options. Reliability and validity of the questionnaires was confirmed by Cronbach's alpha and test-retest coefficient. The data collected before and 2 months after training were analyzed with SPSS 20 and Chi-square, pair and independent t-test, and Fisher's exact test. Results: The mean scores of attitude (from 26.3±17.4 to 45.7±21.6), subjective norms (from 20.4±14.6 to 33.4±15.2), perceived behavioral control (from 36.6±20.9 to 58.4±27.3), intention (from 6.24±2.2 to 11.4±3.8) and addiction related preventive behavior (from 24.11±9.5 to 40.6±13.7) were significantly improved after educational intervention among the experimental group (p < 0.001). Conclusion: TPB provides an appropriate framework for designing educational interventions to prevent substance abuse among adolescents and its application in health promotion programs in schools and prevention of substance abuse is recommended. Paper Type: Research Article.